The state of lipid free radical oxidation and antioxidant system in patients with COVID-19 with concomitant coronary heart disease - Titova, I. S.; Kopiika, V. V.; Shvets, V. M.; Швець, Володимир Миколайович (Харків : НФаУ, 2022)
The aim of the study is to study the processes of free radical oxidation of lipids, and the state of the enzymatic system of cell protection against free radical damage in patients affected by COVID-19 and concomitantly suffering from coronary heart disease.
Keywords: COVID-19; lipid free radical oxidation; SOD; dyne conjugates; malondialdehyde; oxidative stress